Progress in Xenotransplantation: Immunologic Barriers, Advances in Gene Editing, and Successful Tolerance Induction Strategies in Pig-To-Primate Transplantation - Eisenson, Daniel L.; Hisadome, Yu; Yamada, Kazuhiko (Frontiers in Immunology, 2022)
Organ transplantation is the most effective treatment for end stage organ failure, but there are not enough organs to meet burgeoning demand. One potential solution to this organ shortage is xenotransplantation using pig tissues. Decades of progress in xenotransplantation, accelerated by the development of rapid genome editing tools, particularly the advent of CRISPR/Cas9 gene editing technologies, have enabled remarkable advances in kidney and heart xenotransplantation in pig-to-nonhuman primates. These breakthroughs in large animal preclinical models laid the foundation for three recent pig-to-human transplants by three different groups: two kidney xenografts in brain dead recipients deemed ineligible for transplant, and one heart xenograft in the first clinical grade study of pig-to-human transplantation. However, despite tremendous progress, recent data including the first clinical case suggest that gene-modification alone will not overcome all xenogeneic immunologic barriers, and thus an active and innovative immunologic strategy is required for successful xenotransplantation. This review highlights xenogeneic immunologic barriers, advances in gene editing, and tolerance-inducing strategies in pig-to-human xenotransplantation.